Formal Treatment of Definiteness in Arabic - Raii, Jalal (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper analyzes the views of transformational linguists on the definite article with special reference to how it is generated. It also gives a formal representation of the possible configurations in a DP with a definite article al in Arabic. It also tries to account for the generation of a DP that contains the definite article al and the indefinite article in Arabic.